Kepemimpinan Pemberdayaan Dalam Memfasilitasi Peningkatan Kreativitas Karyawan Di Era 4.0: Peran Efikasi Diri Kreatif Dan Religiosity - Santi Retno Sari; Dita Nurul Aini Mustika Dewi; Kumba Digdowiseiso (LPMP Imperium, 2022)
This study aims to analyze and test the factors that increase employee creativity. This study examines moderating religiosity on the relationship between leadership, empowerment and employee level mediated by creative self-efficacy among employees in Jakarta. The research population was taken from the academic community of the National University, including employees, working students and alumni who have worked. The data was collected using a survey method by distributing questionnaires. The sample measurement was based on consideration of the good social research sample size according to the experts and was determined at 150. The sampling technique used was convenient sampling. The analytical method used in this research is testing moderation mediation with Macro Process 3.15V with model 15. The results show that leadership empowerment increases employee creativity both directly and indirectly. The indirect effect of empowerment leadership on employee creativity is through an increase in employee creative self-efficacy. The results also show additional insight that the level of employee religiosity moderates the influence of empowerment leadership on creativity in a negative direction. But the level of religiosity does not moderate the effect of employee creative self-efficacy on employee creativity. Practical implications are presented in this study.